Review of parameters influencing the structural response of a submerged body under cavitation conditions. (November 2015) - Escaler, X; De La Torre, O; Farhat, M
Abstract: Submerged structures that operate under extreme flows are prone to suffer large scale cavitation attached to their surfaces. Under such conditions the added mass effects differ from the expected ones in pure liquids. Moreover, the existence of small gaps between the structure and surrounding bodies filled with fluid also influence the dynamic response. A series of experiments and numerical simulations have been carried out with a truncated NACA0009 hydrofoil mounted as a cantilever beam at the LMH-EPFL cavitation tunnel. The three first modes of vibration have been determined and analysed under various hydrodynamic conditions ranging from air and still water to partial cavitation and supercavitation. A remote nonintrusive excitation system with piezoelectric patches has been used for the experiments. The effects of the cavity properties and the lateral gap size on the natural frequencies and mode shapes have been determined. As a result, the significance of several parameters in the design of such structures is discussed.